2016
DOI: 10.1007/s13224-016-0958-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Preeclampsia in Early Pregnancy by Estimating the Spot Urinary Albumin/Creatinine Ratio

Abstract: A spot urinary albumin-to-creatinine ratio of more than 9.8 mg/g of creatinine can predict the development of preeclampsia in later pregnancy with the sensitivity and specificity of 67 and 76%, respectively. However, additional studies and cost-benefit analysis are required to confirm these finding before recommending this test for screening purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…The studies done by Poon et al, Upadhyay A et al, Devi LT et al, and Gupta et al showed that the URINE ALBUMIN TO CREATININE RATIO(UACR) values were significantly higher in the preeclampsia group when compared to the normotensive group with significant p-value. [24][25][26] In the present study, the sensitivity and specificity of spot urine albumin to creatinine ratio in the prediction of preeclampsia was 85% and 91%, respectively. Therefore, the spot UACR may be helpful to predict early onset preeclampsia.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The studies done by Poon et al, Upadhyay A et al, Devi LT et al, and Gupta et al showed that the URINE ALBUMIN TO CREATININE RATIO(UACR) values were significantly higher in the preeclampsia group when compared to the normotensive group with significant p-value. [24][25][26] In the present study, the sensitivity and specificity of spot urine albumin to creatinine ratio in the prediction of preeclampsia was 85% and 91%, respectively. Therefore, the spot UACR may be helpful to predict early onset preeclampsia.…”
Section: Discussionsupporting
confidence: 48%
“…Gupta et al shows the Cesarean section rate is significantly higher in the preeclampsia group when compared to the normotensive group. 27 (p value 0.001). But as per Zadeh et al, there was no significant difference observed in type of delivery between Preeclampsia and normotensive groups.…”
Section: Discussionmentioning
confidence: 97%
“…Gupta et al showed the cesarean section rate is significantly higher in the preeclampsia group when compared to the normotensive group (p value 0.001). 26 But as per Zadeh et al, there was no significant difference observed in type of delivery between preeclampsia and normotensive groups. 18 Our study findings found to be consistent with Zadeh et al study showing no statistically significant difference between 2 groups (p=0.149).…”
Section: Discussionmentioning
confidence: 80%
“…Singh et al (2015) identified the presence of microalbuminuria at 28-30 weeks of gestation to be predictive of subsequent preeclampsia with an odds ratio of 2.1 (95% CI 1.26-3.53). Another study showed that microalbuminuria at 10-12 weeks of gestation had 50% of sensitivity, 58% specificity, 50% PPV and 91% NPV for the later development of preeclampsia (Gupta et al, 2017).…”
Section: Discussionmentioning
confidence: 99%